A Systematic Scoping Review of Human-Dog Interactions in Virtual and Augmented Reality: The Use of Virtual Dog Models and Immersive Equipment - Oxley, James Andrew; Santa, Kristof; Meyer, Georg; Westgarth, Carri (Frontiers in Virtual Reality, 2022)
Virtual reality is beneficial from a research and education perspective as it allows the assessment of participants in situations that would otherwise be ethically and practically difficult or impossible to study in the real world. This is especially the case where the assessment of human behaviour in the presence of stimuli (e.g. an aggressive dog) is being measured which could potentially constitute a risk in a real-world environment (e.g. a dog bite). Given that the dog is the most popular companion animal species, to date there is limited research that identifies and reviews the use of virtual and augmented reality directly relating to human-dog interactions. Furthermore, there also appears to be no review of the equipment and dog model specifications, such as dog breed and behaviours, which are currently used in these studies. As a result, this systematic scoping review searched ten databases to assess the current use and specifications of dog models which directly focused on human-dog interactions. Ten articles were identified. Six related to assessment or treatment of dog fear/phobia (cynophobia), three included multiple animal phobias, including dogs, and one article investigated the human and virtual dog interactions whilst walking. Six articles used a single breed (German Shepherd, Beagle, Doberman, and Rottweiler). Both the breed and behaviours displayed lacked justification and were often not evidence based. Specific measurements of model quality (e.g., polygons/vertices) were reported in only two articles which may affect repeatability and make comparisons between studies difficult. The virtual reality equipment (e.g. CAVE, head mounted display) and navigation methods (e.g. joystick, mouse, room scale walking) used varied between studies. In conclusion, there is a need for the accurate development and representation, including appearance and behaviours, of dog models in virtual and augmented reality. This is of high importance especially as most of the research covered in this review was conducted with the aim to treat the fear or phobia of dogs.